The Postmodern-Postcolonial Synergic Interfaces in Chinua Achebe’s Anthills of the Savannah - Choudhury, Monir A (Journal of Ecohumanism, 2025)
This study explores the postmodern attitudes, approaches, and perspectives in Chinua Achebe’s 1987 novel Anthills of the Savannah. It seeks to demonstrate how this novel navigates the readers to believe that African outlooks and world views align with the postmodern attitudes towards life and the world. Using postmodernist and postcolonial approaches as methodological tools to analyze the text has become an absolute must as the study envisages critically mapping a territory where both the postmodern and postcolonial approaches towards life and the world have synergic interfaces and complement each other. The study has also used extensively Jean-Francois Lyotard’s key postmodernist concept of ‘mini-narratives’ to analyze some of the key passages of the text. The findings reveal that Achebe has underscored the values of the mini-narratives in building a culturally influential nation and suggested how to connect them for synergic results. In conclusion, this study argued that if a postcolonial society aspires to regain its lost dignity and identity, it does not necessarily mean it will return to its past cultural heritage and will be in binary opposition with the West.